Stability Evaluation on Diminazene Diaceturate and Phenazone in Bulk and Combined Formulations using Validated Chromatographic Method - Mubarak, Amna; Shantier, Shaza Wagiealla; Mohamed, Magdi Awadalla; Gadkariem, Elrasheed Ahmed (Borneo Journal of Pharmacy, 2024)
The combined therapy of diminazene aceturate (DMZ) and phenazone (PHENZ) is widely used in veterinary medicine to combat trypanosomiasis and babesiosis. This study presents a novel, validated HPLC method for accurately quantifying DMZ and PHENZ in various pharmaceutical formulations, including bulk powders, sachets, vials, and injectables. The chromatographic separation was achieved using a C18 column (150 x 4.6 mm, 5 μm particle size) with a mobile phase composed of phosphate buffer (pH 3.0) and methanol (70:30 v/v) at a flow rate of 1 mL/minute. UV detection was set at 250 nm. The method demonstrated linearity over a concentration range of 20-100 μg/mL for DMZ and 25-125 μg/mL for PHENZ, with correlation coefficients exceeding 0.999. Forced degradation studies were conducted under various stress conditions to assess the method's stability-indicating power. DMZ exhibited first-order degradation under acidic pH conditions. While slight degradation (2.4-3.1%) was observed under alkaline, UV, and indoor room light conditions, PHENZ remained stable. The validated HPLC method effectively quantified DMZ and PHENZ in the presence of their degradation products and impurities, demonstrating its suitability for quality control and stability studies of these combined drug formulations.